2004
DOI: 10.1038/sj.ejcn.1601786
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D insufficiency in healthy elderly people living at home in Argentina

Abstract: Objective: To evaluate the nutritional status of vitamin D in urban populations of healthy elderly people living at home, in different regions of Argentina. Design: Cross-sectional study. Subjects: In total, 386 ambulatory subjects over 65 y of age from seven cities (between latitude 261S and 551S) were asked to participate between the end of winter and the beginning of spring. Of these, 369 accepted, 30 were excluded because of medical history or abnormal biochemical determinations. Finally, 339 subjects (226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 30 publications
(44 reference statements)
5
49
0
4
Order By: Relevance
“…Asian migrants that moved to northern countries and Canadian summer holiday takers that travelled closer to equatorial latitudes showed a decrease and increase in their vitamin D levels respectively, confirming this relationship [17][18][19]128]. Furthermore, in Argentina, vitamin D deficiency is significantly lower in populations living in northern regions where mean latitude, temperature, and heliophany (daily hours of solar irradiation) varied from 48°S to 27°S, 3.7°C to 16.1°C, and 3.6 h to 6.3 h of UV irradiation, respectively [78]. The findings from China, although in different population groups, also indicate much lower 25(OH)D levels in northern latitudes [42,45].…”
Section: Latitude and Seasonsupporting
confidence: 62%
See 1 more Smart Citation
“…Asian migrants that moved to northern countries and Canadian summer holiday takers that travelled closer to equatorial latitudes showed a decrease and increase in their vitamin D levels respectively, confirming this relationship [17][18][19]128]. Furthermore, in Argentina, vitamin D deficiency is significantly lower in populations living in northern regions where mean latitude, temperature, and heliophany (daily hours of solar irradiation) varied from 48°S to 27°S, 3.7°C to 16.1°C, and 3.6 h to 6.3 h of UV irradiation, respectively [78]. The findings from China, although in different population groups, also indicate much lower 25(OH)D levels in northern latitudes [42,45].…”
Section: Latitude and Seasonsupporting
confidence: 62%
“…This study showed a cut-off level of 25(OH)D of 68 nmol/L at which serum PTH began to increase [78]. Another study in ambulatory women from Buenos Aires showed differences in 25(OH)D levels in summer (63 nmol/L) and winter (53 nmol/L) [79].…”
Section: Latin Americamentioning
confidence: 98%
“…The frequency of vitamin D insufficiency observed in our study is considerably higher than that reported by Fradinger et al [19] who found that 46.4% of patients from a sample of 198 postmenopausal women of similar average age to the patients in this study, living in the city of Buenos Aires (Latitude: 34˚S) had less than 30 ng/ml. The average value of 25(OH)D observed in our sample (22.4 ± 8.6 ng/ml) is similar to that found by Oliveri et al [13] in another study carried out in 364 volunteers from different regions of Argentina. However, the mean age of our patients was lower than that cited by this group.…”
Section: Discussionsupporting
confidence: 77%
“…Prevalence of hypovitaminosis D has been studied in a sample of 339 healthy adults from different regions of Argentina. The mean serum 25(OH)D was lower in the South (14.2 ± 5.6 ng/ml) compared to that in the Northern and Central regions (20.7 ± 7.4 ng/ml, and 17.9 ± 8.2 ng/ml, respectively) [13].…”
Section: Introductionmentioning
confidence: 99%
“…25-Hydroxyvitamin D insufficiency has been commonly described in the institutionalized older population of the northern hemisphere, but it has recently been proposed that insufficiency may indeed be more common in the general population than previously thought (Chapuy et al, 1996(Chapuy et al, , 1997bJacques et al, 1997;Bettica et al, 1999;Aguado et al, 2000;Inderjeeth et al, 2000;Oliveri et al, 2004). Combination calcium and vitamin D are commonly given for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%